The effect of exercise and adrenaline stimulation of the fibrinolytic enzyme system in young men and women - Cash, J. D. (The University of Edinburgh, 1966)
The euglobulin lysis time before and after moderate exercise and before and after intravenous adrenaline has been studied in normal subjects between the ages 18 -30 years. The resting euglobulin lysis time varied from subject to subject and from day to day in the same subject. There was a highly significant lower level in the females. There was no correlation in the resting levels of euglobulin lysis time with the menstrual cycle.

The fibrinolytic reactivity to moderate exercise and intravenous adrenaline was reproducible in anyone individual, but there was significant difference in reactivity between individuals, which revealed the presence of a group of consistently poor reactors. The fibrinolytic reactivity in women, of the same age group, was significantly greater than men, but there appeared to be no changes coincident with the phases of the menstrual cycle.

The possible significance of these findings are discussed in the light of Astrup's hypothesis of the aetiology of atherosclerosis and /or thrombosis.
The effect of exercise and adrenaline stimulation of the fibrinolytic enzyme system in young men and women: William Leslie Prize in Medicine, 1966